2008
DOI: 10.2320/matertrans.mra2008603
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Sintering of Ni-Based Bulk Metallic Glass Matrix Composite in a Single-Mode Applicator

Abstract: Microwave (MW) heating and sintering of Ni-based bulk metallic glass matrix composite, consisting of gas-atomized Ni 52:5 Zr 15 Nb 10 Ti 15 Pt 7:5 glassy alloy and tin powders, was performed without external pressure by using a single-mode applicator. These powders could be heated well in the magnetic field maximum, but not heated enough in the electric field maximum. A bulk sintered body with the retention of the amorphous phase was obtained below 783 K in an inert atmosphere. The addition of Sn particles pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…A similar result was also observed in previous studies. [15,16] With an increase of the Sn addition contents, the relative density of obtaining sintered bulk samples increased. Table I gives the measured relative density of the sintered bulk samples containing various Sn addition contents at various sintering temperatures.…”
Section: B Mw-induced Sintering Behaviormentioning
confidence: 96%
See 2 more Smart Citations
“…A similar result was also observed in previous studies. [15,16] With an increase of the Sn addition contents, the relative density of obtaining sintered bulk samples increased. Table I gives the measured relative density of the sintered bulk samples containing various Sn addition contents at various sintering temperatures.…”
Section: B Mw-induced Sintering Behaviormentioning
confidence: 96%
“…[7,8] The microwave sintering of various metallic powders, steels, and nonferrous alloys produced sintered samples within tens of minutes at sintering temperatures between 1370 and 1570 K. [9][10][11][12] Moreover, nanomaterials and some composite materials were produced by the MW sintering technique. [13][14][15][16][17][18] The Ni-based bulk metallic glasses (BMGs) exhibit high thermal stability, ultrahigh strength, and excellent corrosion resistance. [19] Recently, Ni-based BMG rods with diameters up to 2 to 5 mm in various Ni-based metal-metal alloy systems were produced using a Cu mold casting technique; [20][21][22][23] those with a diameter of 15 mm in the metal-metalloid Ni-Pd-P-B alloy system were prepared by a water quenching technique along with flux treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we attempted to consolidate Ni-based metallic glass alloy powders and its mixed powders blended with crystalline particulates by the microwave-induced heating and sintering process [14][15][16][17]. It was shown that heating was more efficient in a magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…18,19) Especially microwave radiation has also been successfully used for heating metallic glassy powders and their mixed powders blended with crystalline particulates without pressure. [20][21][22] Compared to conventional heating and sintering, microwave heating can provide some significant advantages such as direct volumetric heating, substantial energy savings, reduction in processing time and lower environmental hazards.…”
Section: Introductionmentioning
confidence: 99%